Helianthus Tuberosus L. (Jerusalem Artichoke) Separation of Extractive Substances of the Plant and Their Chemical Analysis (Eurasian Scientific Herald, 2022)
In this article, the useful properties of the Jerusalem artichoke plant to the human body are given information on the separation of ash, moisture and extractive substances contained in the plant and their chemical analysis